Affective and Cognitive Processes in Cancer Narratives - Monica Kah Pei, Liaw; Ting, Su Hie; Kee Man, Chuah; Collin, Jerome (Chulalongkorn University, 2022)
Research on cancer narratives has not contextualised emotional and cognitive processes in stages of coping. The study examined linguistic indicators of affective and cognitive processes in narratives of 31 Malaysian cancer survivors. The analysis of the 58,787-word transcript using Linguistic Inquiry and Word Count (liwc) software revealed that coping with cancer is a case of mind over emotions, with 12.52% of words related to cognitive processes and 4.17% to affective processes. Frequently used words linked to cognitive processes indicated the cancer survivors’ rationalisations of their denial of the diagnosis and explanations of treatment. Frequently used positive affective words reflect their optimism after reaching acceptance. Frequently used negative affective words indicate their trauma and uncertainty about the prognosis and treatment. Linguistic indicators of emotional and cognitive processes may be useful in identifying stages of coping so that appropriate support can be given to cancer patients and survivors.